2009
DOI: 10.3346/jkms.2009.24.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin A Receptor Blockade Influences Apoptosis and Cellular Proliferation in the Developing Rat Kidney

Abstract: Endothelin systems are believed to play important roles in the emergence and maintenance of functions of various organs during perinatal development, including the kidney. The present study was designed to investigate the roles of endothelin systems on physiologic renal growth and development. Newborn rat pups were treated with either Bristol-Myers Squibb-182874 (30 mg/kg/day), a selective endothelin A receptor (ETAR) antagonist, or vehicle for 7 days. To identify cellular changes, kidneys were examined for ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The eff ect of centhaquin on prenatal and postnatal development has not been studied. It has been advocated that the endothelin (ET) system plays an important role in the emergence and maintenance of various organs and their functions during prenatal development [ 8 ] . Targeted disruption of ET-1 gene in mouse embryonic stem cells led to death of these mice at birth due to respiratory failure and produced malformation of craniofacial tissues, indicating the involvement of ET-1 in normal ontogeny [ 9 ] .…”
Section: Repeated Administration Of Centhaquin To Pregnant Rats Did Nmentioning
confidence: 99%
“…The eff ect of centhaquin on prenatal and postnatal development has not been studied. It has been advocated that the endothelin (ET) system plays an important role in the emergence and maintenance of various organs and their functions during prenatal development [ 8 ] . Targeted disruption of ET-1 gene in mouse embryonic stem cells led to death of these mice at birth due to respiratory failure and produced malformation of craniofacial tissues, indicating the involvement of ET-1 in normal ontogeny [ 9 ] .…”
Section: Repeated Administration Of Centhaquin To Pregnant Rats Did Nmentioning
confidence: 99%
“…Several publications report that ET A receptor activation promotes cell proliferation and cell survival in a rat model of polycystic kidney disease (PKD) (16) during kidney development (41), in vascular smooth muscle cells (34), or in cardiomyocytes (27), whereas others describe pro-apoptotic effects of the ET A receptor in a model of chronic renovascular disease (19). Furthermore, ET Bselective agonists decreased apoptosis in rat endothelial cells (33) and ET B antagonists lead to increased apoptosis in rat and human endothelial cells (11,32).…”
Section: Et-1 Pathway Apoptosis and Renal Injurymentioning
confidence: 99%
“…Apoptosis has been associated with the reduction in renal glomerular number in a rat IUGR model induced by bilateral uterine artery ligation . Imbalance between proliferation and apoptosis has been widely known to play an important role in a variety of physiological processes, such as embryonic growth, development, proliferation of cells, or in a variety of pathological processes such as autoimmune diseases, tumours, and organ damage . A variety of adverse factors, such as hypoxia and malnutrition, can break the balance between apoptosis and proliferation and cause pathological changes in the kidneys, such as reducing the number of glomeruli .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Imbalance between proliferation and apoptosis has been widely known to play an important role in a variety of physiological processes, such as embryonic growth, development, proliferation of cells, or in a variety of pathological processes such as autoimmune diseases, tumours, and organ damage. 24 A variety of adverse factors, such as hypoxia and malnutrition, can break the balance between apoptosis and proliferation and cause pathological changes in the kidneys, such as reducing the number of glomeruli. 9,25 In this study, no significant difference in the proliferation index was observed between IUGR pups and control pups whose mothers were fed a normal diet.…”
Section: Apoptosis In the Kidney Of Iugr Ratsmentioning
confidence: 99%